Oxidation and Reduction of tert-Butylnitrosoacetylene - Jean-Claude Motte; H.G. Viehe (CHIMIA)
Tert-butylnitrosoacetylene [I] can be oxidized to the corresponding nitroacetylene [II] in spite of the low temperature rearrangement of [I] to the isomeric pivaloylcyanide [III]. [I] is reduced with triethylphosphite to an intermediate which reacts with tetramethylethylene formally as the cyanocarbene [VI] rather than as the ethinylnitrene [V].